The Epidemiology of Hypertension in Uganda: Findings from the National Non- Communicable Diseases Risk Factor Survey - Guwatudde, David; Mutungi, Gerald; Wesonga, Ronald; Kajjura, Richard; Kasule, Hafisa; Muwonge, James; Ssenono, Vincent; Bahendeka, Silver K. (PLoS ONE, 2015)
Hypertension is an important contributor to global burden of disease and mortality, and is a growing public health problem in sub-Saharan Africa. However, most sub-Saharan African countries lack detailed countrywide data on hypertension and other non-communicable diseases (NCD) risk factors that would provide benchmark information for design of appropriate interventions.We analyzed blood pressure data from Uganda’s nationwide NCD risk factor survey conducted in 2014, to describe the prevalence and distribution of hypertension in the Ugandan population, and to identify the associated factors.
Keywords: Epidemiology; Hypertension; Uganda; National Non- Communicable Diseases; Survey